The Interest in Developing Fruit and Vegetables “Box Schemes” In Romania - Maria C. DIACONEASA; Alina ZAHARIA; Daniela POPA (Communications of International Proceedings, 2021)
The “box schemes” fit well in the current context of being more sustainable in every aspect of our lives, including our choices of food. Choosing food products that are healthier, but also environmentally and social friendly has started to raise the interest of consumers, while serving as a small business opportunity for farmers. As a form of short supply chain, the box schemes, especially for fruit and vegetables have become a form of affirming your sustainable involvement in Western Europe but have only emerged in Romania. The current study aims at determining if there is a real opportunity for developing this type of short-supply chain in Romania by analyzing the interest shown so far for them in this country compared to other European countries. The results point out that the slight increase in interest shown in Romania for box schemes is a good sign and that by following the examples of more developed countries in this area, this form of short supply chain has development potential. Nevertheless, the study should be further expanded to include other types of analysis for providing more detailed results.
Keywords: Short-Supply Chain; Box Scheme; Fruit and Vegetables; Delivery; Sustainable Choice.